Sustaining Digital Health Interventions for Long-Term Cardiovascular Disease Prevention in the Energy Industry - Isnadi, Yul; Kurniawidjaja, L. Meily; Ramdhan, Doni Hikmat (Kesmas, 2025)
Cardiovascular disease (CVD) is a major health concern for energy industry workers due to occupational risks. Digital health interventions (DHIs) offer innovative strategies for CVD prevention in this high-risk group. This study aimed to explore the effectiveness and sustainability of DHI by incorporating behavior change theories, behavior change techniques, and principles of persuasive system design. A literature review was performed using PubMed, Scopus, Web of Science, and CINAHL databases to collect relevant information on interventions for CVD prevention among energy sector workers. The results indicated that while DHI could improve physical activity, dietary habits, and medication adherence in the short term, sustaining these changes remained challenging due to intervention fatigue, lack of ongoing support, and changing user engagement. To maintain long-term effectiveness, strategies including adaptive interventions, gamification, social support, and iterative refinement based on user feedback are essential. Furthermore, employing a user-centered design approach and integrating DHIs with existing health programs can further enhance sustained behavior change. In conclusion, DHI holds significant potential for CVD prevention in the energy industry. However, its long-term success requires structured approaches, personalized strategies, and ongoing evaluation tailored to this unique occupational setting.